2019
DOI: 10.1038/s41598-019-44508-5
|View full text |Cite
|
Sign up to set email alerts
|

α′ formation kinetics and radiation induced segregation in neutron irradiated 14YWT nanostructured ferritic alloys

Abstract: Nanostructured ferritic alloys are considered as candidates for structural components in advanced nuclear reactors due to a high density of nano-oxides (NOs) and ultrafine grain sizes. However, bimodal grain size distribution results in inhomogeneous NO distribution, or vice versa. Here, we report that density of NOs in small grains (<0.5 µm) is high while there are almost no NOs inside the large grains (>2 µm) before and after irradiation. After 6 dpa neutron irradiation at 385–430 °C, α′ precipitation has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…J o u r n a l P r e -p r o o f 4 Recently, the radiation-induced segregation or depletion of Cr at grain boundaries in nuclear materials of ferritic and austenitic stainless steels have generated considerable research interest [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It was reported by Marquis et al that the radiation-induced depletion of Cr in the ferritic stainless steels is observed by atom probe tomography (APT) when the grain boundaries are segregated with Cr and C in the absence of Cr-carbide phase [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…J o u r n a l P r e -p r o o f 4 Recently, the radiation-induced segregation or depletion of Cr at grain boundaries in nuclear materials of ferritic and austenitic stainless steels have generated considerable research interest [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It was reported by Marquis et al that the radiation-induced depletion of Cr in the ferritic stainless steels is observed by atom probe tomography (APT) when the grain boundaries are segregated with Cr and C in the absence of Cr-carbide phase [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The FeCrAl alloy has a low fraction of second-phase particles having sizes ranging between~100 nm and~3 µm. On the other hand, 14YWT alloys have a high density (~6 × 10 23 m −3 ) of NO (Y-Ti-O) particles [18,[20][21][22]. The red arrows in these figures indicate the second-phase particles.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] A particular field of technology where the potential application of nanocrystalline alloys has been under active consideration is in the selection of appropriate structural materials for the next generation of fission and fusion reactors, by mitigating the generation and by controlling the diffusion of crystal defects at the nanoscale. [23][24][25][26][27][28][29][30][31] An increased density of grain boundaries acting as active sinks for crystalline defects produced from energetic collisions has been recently reported to be the main reason of enhanced radiation resistance of many metals and alloys when compared with their coarse-grained alloy counterparts. [26][27][28] The major challenge for application of nanocrystalline materials in extreme environments remains to prevent the manifestation of degradation mechanisms resulting in microstructural instabilities such as grain growth 24,26,[30][31][32][33][34][35][36] and phase transformations.…”
Section: Introductionmentioning
confidence: 99%